KUALITAS PELAYANAN PADA PASIEN RAWAT JALAN DI PUSKESMAS AMPIBABO KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Rizkiana, Astri (Katalogis, 2020)
This research uses a qualitative approach, research is conducted at the health center location Ampibabo district of Parigi Moutong. The informants are those deemed most know the phenomenon to be studied. Withdrawal techniques using proporsive sampling technique. The type of data used consisted of primary and secondary data. Techniques of data collection consists of observation, interview and documentation. Analysis of the data consists of data collection, data presentation, inference, condensation data. The teory used is the teory of Parasuraman et al. comprising tangible, reliability, responsivenes, assurance and empaty. The results showed that the Quality In Outpatient At Ampibabo Public Healt Center In Ampibabo District Parigi Moutong, consisting of reliability, responsiveness and assurance showed a good level of service quality because of all these aspect nothing is obstructing the quality of public service. While the tangible aspect and empathy, there are obstacles that stiil exist officer who lack discipline in providing services to patients and there are those with less friendly to patients.Â Â